Proceedings of the 15th International Conference on ION Sources, 9-13 September 2013, Chiba, Japan - Pardo R. C. Richard; Brown I. G. Ian (Review of Scientific Instruments Vol. 85. № 2 Part 2 of 2, 2014)
The 15th International Conference on Ion Sources, ICIS' 13, was held on 9-13 September 2013 in Chiba, Japan. The city is the site of the National Institute of Radiological Sciences (MRS) and of the world's first Heavy Ion Medical Accelerator in Chiba (HIMAC). Research on ion sources has a long history. Today it is the core technology for a modern fully flourishing ion beam application industry. Ion sources are now specialized in various applications through a long history of research and development. Each research society develops these specialized ion sources. The International Conference on Ion Sources (ICIS) is the most comprehensive academic conference in the field of ion source research. There is no doubt that every ICIS has encouraged the further advancement of ion sources through fruitful discussions among specialists.